Testo. Dialogo. Traduzione. Per una analisi del tedesco tra codici e varietà - Maria Chiara, Mocali (Biblioteca di Studi di Filologia Moderna, 2009)
"Testo. Dialogo. Traduzione. Per una analisi del tedesco tra codici e varietà" applies the terminology and methods of various subfields addressing textual analysis in German, namely textual linguistics, semiotics, pragmatics, speech linguistics and linguistic psychology, which are brought together in this study to attempt to develop, along with the specific research, a methodology for the science of the text in its general characteristics. Some translations of the nineteenth-century humorist Wilhelm Busch, the Italian version of a key test of the Bauhaus and the transcription of the TV electoral duel of 2005 between Angela Merkel and Helmut Schröder illustrate the broad chronological and typological spectrum of the investigation.